(untitled) (Research, Society and Development, 2022)
Objectives: to recognize the difficulties of leadership practices highlighted by nurse managers in the hospital environment of the public service. Method: this is an exploratory, descriptive research, with a qualitative approach and of an applied nature. Five nurse managers participated in a public hospital in the Metropolitan Region of São Paulo, being interviewed individually in July 2021, after signing the Consent Form. Results and discussion: the coordinating nurses pointed out the existence of a fragility in the competences related to the confrontation of conflicts, evaluation and safety in the application of sanctions to the assistant nurses’ subordinates. Conclusion: it is concluded that there is a need to develop the leadership skills of nurses in public hospitals, which will have an impact on the good progress of the teams and consequent improvement in the quality of care.